EMOTIONAL INTELLIGENCE OF A MEDIATOR AS A TOOL FOR DEVELOPING CONFLICT MANAGEMENT COMPETENCE - DEMCHENKO, Oksana; SEDASHOVA, Oksana; KORNIIENKO, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The work reveals the concept of emotional intelligence as a person's integrative ability to understand their own and other people's emotions, as well as to manage them. The similarity between the concepts of emotional intelligence and emotional competence is highlighted. The concept of "emotional competence" is revealed as a set of knowledge, skills and abilities that help a person to realize and accept their own emotions, themselves, to realize the emotions of others for self-motivation, to manage emotions, to emotionally improve themselves, moving towards self-actualization, creating relationships with others on their way. The role of emotional intelligence is determined as a set of knowledge about adequate behavior in situations of social interaction, which can be useful for preventing and resolving conflicts, in the professional activities of a mediator. It has been determined that in a situation where the conflict cannot be resolved using alternative dispute resolution methods, or if the conflict has reached a stage where resorting to negotiations becomes impossible, in particular for psychological reasons, the most effective way to resolve the dispute, which allows for the full consideration of the interests of the parties and finding a mutually acceptable solution, is mediation. It is determined that it is important for a mediator to determine the factors that influence the destabilization of emotional stability, which forms his emotional intelligence. It is noted that the emotional intelligence of a mediator is an indispensable tool for the formation of his conflictological competence, as the ability to diagnose and resolve conflicts in various areas. It is revealed that the professional knowledge, mediation skills, experience, emotional intelligence and personal qualities of a mediator in resolving conflicts are formed into a single category (conflictological competence), which determines the professional level of the mediator. It is emphasized that for a mediator, both for a professional and for an individual, it is important to develop emotional intelligence, which is due to the complex specifics of his activity - the constant presence of conflicts.
Keywords: emotional intelligence; interaction; emotional competence; communicative management; conflict; mediator